Patient Safety Implementation among Nurse in Inpatient Department at Daha Husada Hospital Kediri - Lia Rosiana Dewi; Amarin Yudhana (Journal of Global Research in Public Health, 2025)
Patient safety is a hospital system aimed at minimizing risks and preventing injury caused by errors in action or inaction. This study aims to explore the implementation of patient safety by nurses at RSUD Daha Husada Kediri using a qualitative case study approach. Data were collected through in-depth semi-structured interviews with inpatient nurses selected by purposive sampling. Source triangulation was used for credibility, focusing on six patient safety goals: patient identification, effective communication, medication safety, correct procedure and site, fall prevention, and infection risk reduction. The findings showed that five of the six safety goals were fully implemented (100%), while others had not achieved maximum outcomes due to nurses' habits, awareness, and lack of routine training. Supporting infrastructure and SOPs were already in place. The study suggests improving orientation for new staff, empowering unit heads as role models, and strengthening routine monitoring and evaluation to ensure consistent and optimal patient safety practices across all units.